Dense-array adjoint tomography reveals lithospheric delamination and asthenosphere upwelling beneath the western Yangtze Craton - Xiao, Zhuo; Sun, Xinlei; Yang, Jianfeng; Gao, Yuan (Frontiers in Earth Science, 2023)
The eastern Tibetan Plateau has attracted widespread attention due to its complex topography and strong seismicity. However, the mechanism controlling the growth of this margin remains enigmatic. Here, we present detailed upper mantle structures of the easternmost and northeastern Tibetan Plateau from dense-array adjoint waveform tomography. The seismic images show mushroom-shaped low-velocity zones atop at the uppermost mantle of the eastern margin of the Tibetan Plateau and slab-shaped high-velocity bodies preserved beneath both the eastern Himalayan syntaxis and the western Sichuan basin. The seismic features suggest asthenosphere upwelling and lithospheric delamination beneath the western Yangtze Craton, which might be induced by the retreat of the subducted Indian Plate. Our study shows that the mantle dynamics of the western Yangtze Craton have played an important role in the Tibetan Plateau growth and suggests that the Yangtze Craton might be reconstructed by ongoing continental collision.